2022
DOI: 10.3390/biology11111671
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sperm Morphology and Altered Sperm microRNA Expression

Abstract: Evaluation of male infertility has been based on semen analysis for years. As this method can be subjective at times, there is a scientific tendency to discover stable and quantifiable biomarkers. This study included 28 couples who underwent an in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycle. The couples were assigned into two groups, according to sperm morphology. Couples where the males were normozoospermic were placed in the control group (15 participants), while couples where males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Over-expression of miR-100 promotes the proliferation of spermatogonial stem cells in vitro ( Huang et al, 2017b ). Another study in human detected significant under-expression of miR-10a-5p in spermatozoa from patients with teratozoospermia ( Tomic et al, 2022 ). The miR-10a-5p is proposed to be related to the proliferation and differentiation of porcine spermatogonia ( Chen et al, 2017 ; Keles et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Over-expression of miR-100 promotes the proliferation of spermatogonial stem cells in vitro ( Huang et al, 2017b ). Another study in human detected significant under-expression of miR-10a-5p in spermatozoa from patients with teratozoospermia ( Tomic et al, 2022 ). The miR-10a-5p is proposed to be related to the proliferation and differentiation of porcine spermatogonia ( Chen et al, 2017 ; Keles et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…The underexpression of predicted miR-296 has been reported in highly fertile men suggesting that overexpression of miR-296 leads to infertility [49]. Additionally, elevated level of miR-296 expression has been also predicted in patients diagnosed with several classes of male factor infertility particularly teratozoospermia, asthenozoospermia, oligozoospermia and normozoospermia indicating characteristic role of miR-296 in inducing infertility [50]. Among impaired spermatogenesis cases of male Korean population, miR-4739-STAG3 interaction has been observed however STAG3 gene is a known hallmark of male factor infertility therefore predicted miR-4739 can be used as therapeutic target against male infertility [41].…”
Section: • Vol 17 • № 5 Obstetrics Gynecology and Reproductionmentioning
confidence: 96%
“…The expression of nine miRNAs, namely miR-10a-5p, miR-15b-5p, miR-26a-5p, miR-34b-3p, miR-122-5p, miR-125b-5p, miR-191-5p, miR-296-5p, and miR-let-7a-5p, was lower in the spermatozoa of patients with teratozoospermia than in those of control individuals. These miRNAs are positively associated with each other, and their abundance is positively associated with spermatozoa morphology ( 31 ). A previous study reported a significant association between the expression of hsa-mir-191-5p and sperm morphology, but no significant association was observed between sperm density and viability ( 27 ).…”
Section: Mirnas and Abnormal Sperm Qualitymentioning
confidence: 99%